Safety assessment of sodium zirconium cyclosilicate: A FAERS-based disproportionality analysis - Yongfei Yu; Kaiyu Zhang; Jinglin Gao; Guoshun Huang; Chen Yong; Yuan Wei; Enchao Zhou (PLoS ONE, 2025)
Sodium zirconium cyclosilicate (SZC) is a novel therapeutic agent for hyperkalemia. However, limited reports have described its real-world safety. In this study, we used the Food and Drug Administration Adverse Event Reporting System (FAERS) database to evaluate the safety profilet of SZC. This retrospective analysis involved FAERS data from the third quarter of 2018 to the fourth quarter of 2023. A disproportionality analysis, including reporting odds ratio (ROR), proportional reporting ratio (PRR), empirical bayesian geometric mean(EBGM), and bayesian confidence propagation neural network (BCPNN), was conducted to quantify the signals of SZC-related adverse events (AEs). Sex subgroup analyses were also conducted. A total of 1,154 SZC-related AE reports were obtained from the FAERS database. SZC-related AEs primarily targeted 21 system organ classes after simultaneously conforming to the four algorithms. The most common AEs included X-ray gastrointestinal tract abnormalities(ROR = 3888.02[1051.8, 14372.15]) and blood potassium abnormal(ROR = 212.53[134.73, 335.26]), consistent with prior findings and clinical trials. Unexpected significant AEs included ileus (ROR = 27.82[14.44, 53.59]), death (ROR = 17.49[15.7, 19.49]) and congestive cardiac failure (ROR = 16.66[10.94, 25.37]). Sex-based differences were observed for AEs. The median onset time of SZC-related AEs was 33 days. This study confirms common AEs of SZC and identifies new ones, highlighting the need for careful monitoring and facilitating its safe use in clinical settings. However, disproportionality analysis cannot formally prove causation and further studies are needed to confirm these associations.